The role of Pt impurities on both bulk and surface anisotropies in amorphous NiMn films - (:unkn) unknown (ELSEVIER SCIENCE BV, 1997)
Electron spin resonance (ESR) measurements have been carried out on amorphous Ni76Mn24 and Ni74Mn24Pt2 films in the temperature range 4-300 K. The spectra at each temperature have been taken for both parallel geometry, where the applied magnetic field is in the surface of the films and perpendicular geometry with the magnetic field perpendicular to the surface. Using computer simulations, the bulk (K) and surface anisotropy constants (Q and k(s)), the exchange stiffness constants (D) and the induced exchange fields (H-exc) were obtained for both films as a function of temperature. At lower temperatures, we were not able to analyse the ESR spectra due to very broad lines, which are associated with the frustration of spins. The frustration manifests itself at higher temperatures for Ni74Mn24Pt2 than for Ni76Mn24 and becomes more severe with Pt impurities. The induced exchange anisotropy, H-exc, which is created during cooling of the sample rotates freely towards the applied field. The temperature behaviour of this anisotropy is in agreement with the exponential law (exp(-alpha/T) for both samples. The exchange stiffness constants, D, of both samples show similar behaviour; D increases with decreasing temperature, slowly at first above certain temperature values (100 K for Ni76Mn24 and similar to 150 K for Ni74Mn24Pt2) and then more rapidly at lower temperatures, being related to the frustration of the system. Furthermore, the deduced bulk and surface anisotropy coefficients from the ESR data analysis revealed that Pt impurities have a considerable influence on the domain structure and, accordingly, the surface anisotropies of the NiMn system.
Keywords: reentrant spin glass; magnetic anisotropy; spin wave resonance; amorphous thin films; REENTRANT SPIN-GLASSES; MN ALLOY; RESISTIVITY; RESONANCE; STATE; TRANSITION; SCATTERING; RESISTANCE; NI76MN24; WAVES